Traditional Health Service Tariffs and Patient Protection in Indonesia: A Legal Perspective - Elijah Alexius Salim; Yana Chaeru Taufik Ismail (Research Horizon, 2026)
Traditional health services in Indonesia have gained formal recognition through Law Number 17 of 2023 concerning Health and Government Regulation Number 28 of 2024. However, these regulations mainly focus on administrative and technical aspects, while tariff regulation remains unaddressed. This study aims to analyze the legal framework governing traditional health services in Indonesia, identify normative gaps related to tariff regulation, and examine their implications for patient protection. This research employs a normative juridical method using statute, conceptual, and analytical approaches. The study relies on primary legal materials, including laws and regulations, supported by legal doctrines and scientific literature related to health law and consumer protection. The findings reveal that the absence of tariff standards creates legal uncertainty and strengthens information asymmetry between practitioners and patients. As a result, patients are placed in a vulnerable position and may experience exploitative pricing practices. Furthermore, the lack of tariff transparency potentially violates Law Number 8 of 1999 concerning Consumer Protection and may fulfill the elements of unlawful acts under Article 1365 of the Indonesian Civil Code through the doctrine of abuse of circumstances. Therefore, comprehensive regulatory reform is necessary to establish transparent, fair, and accountable tariff standards in traditional health services to ensure legal protection and distributive justice for patients.